LSTM based content prediction for edge caching using federated learning approach - Mazumder, Shafkat Ahmed; Paul, Piash; ZUBAIR, DIN MOHAMMAD; Haque, Maksudul; Mayukh, Jidni (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.